Novel Associations Between METTL3 Gene Polymorphisms and Pediatric Acute Lymphoblastic Leukemia: A Five-Center Case-Control Study - Liu, Xiaoping; Huang, Libin; Huang, Ke; Yang, Lihua; Yang, Xu; Luo, Ailing; Cai, Mansi; Wu, Xuedong; Liu, Xiaodan; Yan, Yaping; Wen, Jianyun; Cai, Yun; et al. (Frontiers in Oncology, 2021)
Objective: To reveal the contributing role of METTL3 gene SNPs in pediatric ALL risk. Patients and Methods: A total of 808 pediatric ALL cases and 1340 cancer-free controls from five hospitals in South China was recruited. A case-control study by genotyping three SNPs in METTL3 gene was conducted. Genomic DNA was abstracted from peripheral blood. Three SNPs (rs1263801 C>G, rs1139130 A>G, rs1061027 A>C) in the METTL3 gene were chosen to be detected by taqman real-time polymerase chain reaction assay. Results: That rs1263801 C>G, rs1139130 A>G, rs1061027 A>C polymorphisms were significantly associated with increased pediatric ALL risk was identified. In stratification analyses, it discovered that rs1263801 CC, rs1061027 AA and rs1139130 GG carriers were more likely to develop ALL in subgroups of common B-ALL, MLL gene fusion. Rs1263801 CC and rs10610257 AA carriers were more possibly to increase risk of ALL in subgroups of low hyperdiploid; and all of these three SNPs exhibited a trend toward risk of ALL. All of these three polymorphisms were associated with the primitive/naïve lymphocytes and MRD in marrow after chemotherapy in ALL children. Rs1263801 CC and rs1139130 AA alleles were a protective effect on MRD ≥0.01% among CCCG treated children. As for alleles were a protective effect on MRD in marrow ≥0.01% on 33d and 12 weeks among CCCG treated children, but were risk effect on MRD in marrow ≥0.01% among SCCLG treated children. As for rs1061.27, AA alleles were a risk effect on MRD in marrow ≥0.01% among CCCG treated children. Conclusion: In this study, we revealed that METTL3 gene polymorphisms were associated with increased pediatric ALL risk and indicated that METTL3 gene polymorphisms might be a potential biomarker for choosing ALL chemotherapeutics.